2014
DOI: 10.1103/physrevb.90.165111
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic characterization of iron oxyselenidesCe2O2Fe2OSe2and

Abstract: We present here an investigation of the magnetic ordering in the Mott insulating oxyselenide materials Ln 2 O 2 Fe 2 OSe 2 (Ln = Ce, Nd). Neutron powder diffraction data are consistent with a noncollinear multi-k ordering on the iron sublattice structure and analysis indicates a reduced magnetic correlation length perpendicular to the [Fe 2 O] 2+ layers. The magnetic role of the Ln 3+ cations is investigated and Ce 3+ moments are found to order at T 16 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 37 publications
9
26
0
Order By: Relevance
“…Magnetic Bragg reflections are observed on cooling below ∼90 K in zero field. These reflections, consistent with the 2k magnetic structure reported for Ln 2 O 2 Fe 2 OSe 2 (Ln = La, Nd, Ce) [17,37] and Sr 2 F 2 Fe 2 OS 2 [11], increase smoothly on cooling (Supplemental Material [51]). As for other materials, magnetic reflections are anisotropically broadened, suggesting stacking faults in the magnetic structure perpendicular to the Fe 2 O layers.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Magnetic Bragg reflections are observed on cooling below ∼90 K in zero field. These reflections, consistent with the 2k magnetic structure reported for Ln 2 O 2 Fe 2 OSe 2 (Ln = La, Nd, Ce) [17,37] and Sr 2 F 2 Fe 2 OS 2 [11], increase smoothly on cooling (Supplemental Material [51]). As for other materials, magnetic reflections are anisotropically broadened, suggesting stacking faults in the magnetic structure perpendicular to the Fe 2 O layers.…”
Section: Resultssupporting
confidence: 85%
“…Sequential Rietveld refinements in zero field showed that the unit cell parameters decreased on cooling, similar to behavior reported for other Ln 2 O 2 Fe 2 OSe 2 analogues, with a more rapid decrease in the c parameter below T N , presumably due to magnetostrictive effects [17,37]. However, a slight increase in the c parameter was observed below ∼22.5 K (see Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Ce-Fe oxyselenides, where ordered Ce moments are required to fit the diffraction data and persist to surprisingly high temperatures [4,6,7,11]. An excellent fit to the PND data is achieved using this type of model, and the refined profiles for 2+ .…”
Section: Model 5) the Observation Of Ce Ordering Is Consistent With mentioning
confidence: 94%
“…One important family of compounds is those with general composition Ln 2 O 2 MSe 2 (Ln = La, Ce; M = Mn, Fe, Zn, Cd) [3][4][5][6][7][8][9][10][11] and closely related composition such as La 2 O 2 Cu 2−4x Cd 2x Se 2 [12]. These materials are semiconductors with band gaps varying from ∼0.3 to ∼3.3 eV [1,[3][4][5]8,10,11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%